Belle Prater's boy [compact disc, unabridged] - White, Ruth, 1942- (Listening Library, 1997)
When Woodrow's mother suddenly disappears, he moves to his grandparents' home in a small Virginia town where he befriends his cousin and together they find the strength to face the terrible losses and fears in their lives.